2009
DOI: 10.1038/onc.2009.248
|View full text |Cite
|
Sign up to set email alerts
|

The prolyl cis/trans isomerase cyclophilin 18 interacts with the tumor suppressor p53 and modifies its functions in cell cycle regulation and apoptosis

Abstract: The functional diversity of the tumor suppressor protein p53 is mainly regulated by protein interactions. In this study, we describe a new interaction with the peptidylprolyl cis/trans isomerase cyclophilin 18 (Cyp18). The interaction reduced the sequence-specific DNA binding of p53 in vitro, whereas the inhibition of the interaction increased p53-reporter gene activity in vivo. The active site of the folding helper enzyme Cyp18 was directly involved in binding. The proline-rich region (amino acids 64-91) of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…2). This is in accordance with a previous study, which reported that p53 binds at the CsA-binding site of the cyclophilin protein, Cyp18 [60]. It can be deduced that this might be the reason behind the inhibition of CypD-p53 interaction by CsA.…”
Section: P53 Binds To Cypd At Its Csa-binding Sitesupporting
confidence: 93%
“…2). This is in accordance with a previous study, which reported that p53 binds at the CsA-binding site of the cyclophilin protein, Cyp18 [60]. It can be deduced that this might be the reason behind the inhibition of CypD-p53 interaction by CsA.…”
Section: P53 Binds To Cypd At Its Csa-binding Sitesupporting
confidence: 93%
“…In cancer, it has been suggested that PPIA regulation is controlled by p53 or by the hypoxia inducible factor (HIF)-1a. A causative relationship resulting from the direct interaction between PPIA and p53, has been shown during apoptosis and cell cycle regulation (Baum et al, 2009). P53 is known to interact with several proteins involved in cell proliferation; cell proliferation regulation and cell death regulation, some of which have been identified in this study (see Table 2 for reported evidence of their roles).…”
Section: Pfn1 Overexpression Alters the Expression Of Proteins Involvmentioning
confidence: 91%
“…In various cancers, CypA is directly under the transcriptional control of two critical transcription factors for cancer development: the hypoxia-inducible factor 1 alpha subunit (HIF-1 ) [237] and the tumor suppressor p53 [238]. Moreover, a physical and functional interaction between p53 and CypA was identified to mediate the anti-apoptotic effect of CypA [239]. The cyclophilin inhibitors CsA and sanglifehrin A each can synergistically increase apoptotic cell death in hepatocellular carcinoma cells when combined with cisplatin.…”
Section: Cyclophilin Signaling Pathways In Cancermentioning
confidence: 98%